Gendered Power Relations in The Death on The Nile Film (2022): A Critical Discourse Analysis - Vayevienda Muhammad; Mundi Rahayu (Madah: Jurnal Bahasa dan Sastra, 2024)
This research aims to get the understanding of the representation and dynamics of gendered power relation in the film "Death on the Nile" (2022), by focusing on the social roles and norms that influence the gender relation among characters. The research applies Fairclough’s Critical Discourse Analysis (CDA) which enables us to go deeper on the power relation of the characters. The CDA framework consists of the comprehensive analysis, from the micro (text), mezzo (production), and macro (social context) analysis that can be applied in analysis of the film. The results show that gendered power relations in this film are depicted through the power in marriage relationship, where the concepts of control and ownership reflect the social norms of the society. Power in love relationship also play an important role in relationship dynamics, highlighting how strong feelings and dependency can influence the social practice. In addition, power in parent-children relationship can continue even after children become adults. These findings provide a foundation for further research on the representation of gender-based power relations in film, taking into account the other aspects such as the social, economic, and cultural factors that influence gender representation.